Konflik Sosial Dalam Novel Rembulan Tenggelam Di Wajahmu Karya Tere Liye: Kajian Sosiologi Sastra - Mayviolita Aulia Nur Annisa; Ahmad Rifai; Siti Fatimah (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This research uses the literary object of the novel entitled Rembulan Tenggelam di Wajahmu by Tere Liye. This research is motivated by several social conflicts that usually occur in society, both those that are going through and that have already been passed. The formulation of the problem in this research is how social conflict is in the novel Rembulan Tenggelam di Wajahmu by Tere Liye. The social conflicts in the novel include realistic conflicts, non-realistic conflicts and the positive function of social conflict. The aim of this research is to describe the social conflict in the novel Rembulan Tenggelam di Wajahmu by Tere Liye. This research uses a qualitative descriptive method with a literary sociology approach through Lewis A. Coser's social conflict theory which is used to discover social conflict. The data collection technique in this research uses documentation techniques. Based on the research results, it can be concluded that there is an analysis of social conflict in the novel Rembulan Tenggelam di Wajahmu by Tere Liye: A Sociological Study of Literature which consists of 1) The concept of social conflict of the characters in the form of realistic conflict with elements of Hostile feeling and Hostile behavior  and non-realistic conflicts are dominated by realistic conflicts because the conflicts in the novel mostly occur between two people and without the element of revenge.